PENGARUH KONSENTRASI STARTER TERHADAP PRODUKSI ETANOL DAN KARAKTERISTIK WINE BERBAGI JENIS KETELA RAMBAT (IPOMOEA BATATAS) - Selamet Duniaji, Agus; Wisaniyasa Dewi Sirait, Ni Wayan (Agrotekno, 2014)
Wine is ethanol fermented production by Saccaromyces cereviceae on the severely sugar of grape fruit and other some fruit. Wine was involved cluster of alcoholic’s drink of B classification in Indonesian Standardization code with range alcoholics 5 to 20% which is consideration by the Indonesian Healthy Ministry. The research was aimed to know the effect of starter concentration on ethanol production and wine characteristic of several sweat potato. The experiment used factorial design consist of starter concentration 5%, 10% and 15% while several of sweat potato such as white color sweat potato, yellow color sweat potato and purple color sweat potato. Result of research showed that white color sweat potato and adding 15% starter produced the total of ethanol 16,65% v/v, While the sensory tested indicated that purple color sweat potato and 15 % starter produced the best characterization of wine with the criteria purple colorizes, specific odor and flavor were accepted by panelist. The treatment is also supported by 15 % starter to produce wine with the criteria purple colorizes, specific odor and flavor and all accepted by panelist. The treatment is also supported by pH 3,42, TSS 6,05% brix, total of acetic acid 0,0825% b/v, total of anthocynine 22,92 mg/100g, ethanol content 10,90%, total of fungi 2,20x104cfu/ml. All of the characteristic of wine as well as according to the Indonesian standardization code (SNI-01-4018- 1996). Panelist tested showed that wine preferred
Keywords: Sweat potato, Fermented, Starter and Ethanol /Alcohol